2006
DOI: 10.1111/j.1540-8167.2006.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Dual Atrioventricular Nodal Physiology in Pediatric Patients with Atrioventricular Nodal Reentrant Tachycardia

Abstract: Neither the common definition of dual AV nodes or redefining an AH jump as some value <50 msec are reliable methods to define dual AV nodes or to predict AVNRT in pediatric patients. PR > or = RR is a relatively good predictor of AVNRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
(12 reference statements)
0
25
0
1
Order By: Relevance
“…Additionally, the presence of dual AV node physiology is often not present in pediatric patients with AVNRT. 12 The response of junctional acceleration during a radiofrequency lesion provides an additional method of identifying a successful lesion. 13 This response does not occur during cryoablation lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of dual AV node physiology is often not present in pediatric patients with AVNRT. 12 The response of junctional acceleration during a radiofrequency lesion provides an additional method of identifying a successful lesion. 13 This response does not occur during cryoablation lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a less stringent criterion to define DAVNP might be appropriate in children 16 . Recent data in another cohort of pediatric patients with AVNRT reveal DAVNP in 51%, and an AH “jump” between 30 and 49 ms in 37% 17 . However, 12% had continuous AV conduction curves, suggesting that no single threshold for change in A2H2 interval will define all patients with the substrate for AVNRT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that SSPC during atrial pacing is a good marker for the diagnosis of AVNRT and a useful surrogate endpoint for slow pathway ablation [18, 19]. In the present study, only patients with the slow-fast form of AVNRT were demonstrated to have SSPC during atrial pacing.…”
Section: Discussionmentioning
confidence: 44%